2000
DOI: 10.21236/ada440368
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Trust Biases in the Design of Augmented Reality Displays

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 158 publications
(221 reference statements)
0
17
0
Order By: Relevance
“…Nonlinear assembly sequence graphs are derived in real-time for the generation of adapted instructions. These require environmentally-and situationally dependent triggered paths on state-based graphs [157], [158]. The graph-based structure integrates product states as vertices and assembly operations and their respective complexity as edges [159].…”
Section: Assistance Systems 1) Motivationmentioning
confidence: 99%
“…Nonlinear assembly sequence graphs are derived in real-time for the generation of adapted instructions. These require environmentally-and situationally dependent triggered paths on state-based graphs [157], [158]. The graph-based structure integrates product states as vertices and assembly operations and their respective complexity as edges [159].…”
Section: Assistance Systems 1) Motivationmentioning
confidence: 99%
“…Dopping-Hepenstal reported that "military pilots fixated more frequently on information presented on a HUD at the cost of scanning the outside scene" [28]. Yeh, et al reported that "cueing aided the target detection task for expected targets but drew attention away from the presence of unexpected targets" [29]. Attention tunneling can reduce user performance and generate potentially hazardous scenarios.…”
Section: Effect Of Attention Tunneling In Augmented Realitymentioning
confidence: 99%
“…Although the primary interest of researchers is focused on trainees' observable reactions to contents, measured in terms of time and errors, several authors also proposed to measure physiological reactions of trainees during the performances by gathering data, for instance, through eye-tracking tools -to measure the participants' attentional focus during the procedure [58,59] -or through systems for heart rate analysis -to estimate the cognitive load in performing tasks [60,61]. Moreover, at least two other additional criteria for measuring the improved abilities of the trainees were proposed in literature of VR/MR studies for training.…”
Section: Performance Criteriamentioning
confidence: 99%